Stability Indices for Randomly Perturbed Power Systems - Verdejo-Fredes, H (2014)
This paper considers the stability of moments of stochastic systems, such as stability of the mean or mean-square stability. The exponential growth behavior of moments is compared to almost sure exponential growth via Lyapunov exponents. We develop a series of indices that are useful to describe system performance under random perturbations. The theory is applied to two examples, including an electric power system. © 2014 The Authors. Published by Elsevier Inc. All rights reserved.
Keywords: Stochastic system; Stochastic stability; Lyapunov exponents; Moment stability; Electric power systems